Analysis of Participants' Perceptions of Intermittent Fasting in the Weight Loss Process among Individuals with Obesity - Waldo, Kevin; Putra, Ceppy Pradana; Hasibuan, Mhd. Usni Zamzami; Yusradinafi, Yusradinafi (Jurnal Sains Sosio Humaniora, 2026)
This study aims to analyze participants’ perceptions of practicing intermittent fasting (IF) as a method for weight loss among individuals with obesity. A qualitative descriptive approach was used with a purposive sampling technique involving three participants with varying experiences: a beginner (two weeks), an intermediate participant (three months), and an experienced participant (ten years). Data were collected through in-depth interviews and analyzed thematically. The results show that beginners faced adaptation challenges such as hunger, fatigue, and mood changes, although they began to observe physical improvements. Intermediate participants experienced more stable benefits, including improved fitness, better eating control, and social support. Experienced participants perceived IF as a sustainable healthy lifestyle with positive impacts on both physical and mental health. In conclusion, IF is generally perceived positively, although the initial stage requires adaptation. It is recommended to provide guidance, maintain consistency, and integrate IF with physical activity and balanced nutrition for optimal results.